Effect of Pre-passivation on the Corrosion Behavior of PH13-8Mo Stainless Steel in Industrial—Marine Atmospheric Environment - Liu, Yanning; Zhao, Qiyue; Zhao, Jinbin; Huang, Yunhua; Cheng, Xuequn; Lu, Lin (Frontiers in Materials, 2019)
The corrosion behavior and mechanism of PH13-8Mo stainless steel with and without nitric acid passivated film were studied through 5 years of outdoor exposure tests in industry-marine atmospheric environments in Qingdao, by means of morphological observation, weight-loss measurement, X-ray photoelectron spectroscopy (XPS) and Scanning Kelvin Probe (SKP). The results showed that the pre-passivation certainly inhibits the corrosion, but exhibits an obvious limitation of protection period for PH13-8Mo stainless steel in industrial-marine atmosphere. Compared with bare PH13-8Mo steel, the number and depth of pitting of pre-passivated steel were reduced, and the average corrosion rate decreased by 14.7%. The reasons of improved corrosion resistance included the higher ratio of Cr/Fe and oxide/hydroxide, and the more positive and homogeneous Kelvin voltage potential for the surface of outdoor exposed pre-passivated steel. Meanwhile, the pre-passivation film on the Cr-depleted regions caused by the Cr-rich precipitated phase was preferentially destructed in the atmosphere with Cl-, which decreased the protection period.